Knowledge, higher education and human capital: a case study of professional Master’s programmes in China - Zhang, Xunzhe (2017)
A growing number of master’s programmes have become more professional, but less academic and research-orientated, to meet labour market needs. For example, new professional master’s programmes were introduced in China 2009. They have grown rapidly and now account for almost half the number of full-time master’s entrants. However, why are professional master’s programmes expected to meet labour market needs better? In the related literature, the connection between higher education and the labour market has usually been explained by human capital, and economic evidence has supported this connection. However, few studies have considered why human capital can explain the relationship between higher education and the labour market.